The chaos curse - DasGupta, Sayantani (DasGupta, Sayantani. Kiranmala and the kingdom beyond, 2020)
Twelve-year-old demon slayer Kiranmala and her friends leave the Kingdom Beyond and travel to Parsippany to save Prince Lal who has been trapped in a tree in the yard of Kiranmala's enemy. However, during the mission, reality keeps flickering and causing other stories and worlds to become mixed together. There seems to be an interruption in the multiverse and it appears that Kiranmala's father, the Serpent King, is trying to collapse the parallel dimensions of the multiverse into one in order to destroy its diversity.